The Effect of Smartphone Addiction on Trunk Muscles Performance in Adolescents: A Transverse Study - Elsayed Ayoub, Hamada; Ebrahim Elkomy, Aya; Ahmed Olama, Khaled; Mohamed Kamal, Hebatallah; Salim Mohamed, Ahmed (Journal of Neonatal Surgery, 2025)
Background: Smartphones are widely used among people worldwide but it’s over use can cause smartphone addiction, which was found to cause musculoskeletal problems, as very little number of studies was held to investigate its side effects on the muscles of the trunk. Aim: this research aimed to evaluate the consequences of smartphone addiction on performance of trunk muscles. Methods: Sixty- six adolescent aged 17 and 18 years, were recruited in the research and sorted in addict group (thirty-three participant 17 males and 16 females)or non- addict (control) group (thirty- three participant 17 male and 16 female) according to their score in Smartphone Addiction Scale –Short Version the Arabic version , Isokinetic dynamometer was used for assessment of performance of the muscles of the trunk (trunk flexors and extensors) by evaluating: peak torque per body weight, time to peak torque and agonist to antagonist ratio Results: there were no significant statistical differences between the addict and non-addict group in peak torque per weight of the body, time to peak torque and agonist to antagonist ratio for trunk flexors and trunk extensors Conclusion: from the obtained results, smartphone addiction has no effect on the performance of flexor and extensor muscles of the trunk in adolescents.